2011
DOI: 10.1016/j.jhevol.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative expression analysis of the phosphocreatine circuit in extant primates: Implications for human brain evolution

Abstract: While the hominid fossil record clearly shows that brain size has rapidly expanded over the last ~2.5 M.yr., the forces driving this change remain unclear. One popular hypothesis proposes that metabolic adaptations in response to dietary shifts supported greater encephalization in humans. An increase in meat consumption distinguishes the human diet from that of other great apes. Creatine, an essential metabolite for energy homeostasis in muscle and brain tissue, is abundant in meat and was likely ingested in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 62 publications
(116 reference statements)
1
16
0
2
Order By: Relevance
“…This pattem is consistent with the previous findings in mammals (Jones & MacLamon, 2004;Navarrete et al, 2011) and fish (Warren & Iglesias, 2012). However, most studies testing the expensive-tissue hypothesis have shown that an increase of brain mass has been accompanied by a reduction in gut length across taxa (primates: Aiello & Wheeler, 1995;Aiello, Bates & Joffe, 2001;Pfefferle et al, 2011;fish: Kaufman et al, 2003;cattle: Mau, Südekum & Kaiser, 2009;guppies: Kotrschal et al, 2013). Diet quality as a proxy for gut dimensions may affect brain size evolution (MacLamon, Chivers & Martin, 1986;Isler & Van Schaik, 2006b).…”
Section: Discussionsupporting
confidence: 90%
“…This pattem is consistent with the previous findings in mammals (Jones & MacLamon, 2004;Navarrete et al, 2011) and fish (Warren & Iglesias, 2012). However, most studies testing the expensive-tissue hypothesis have shown that an increase of brain mass has been accompanied by a reduction in gut length across taxa (primates: Aiello & Wheeler, 1995;Aiello, Bates & Joffe, 2001;Pfefferle et al, 2011;fish: Kaufman et al, 2003;cattle: Mau, Südekum & Kaiser, 2009;guppies: Kotrschal et al, 2013). Diet quality as a proxy for gut dimensions may affect brain size evolution (MacLamon, Chivers & Martin, 1986;Isler & Van Schaik, 2006b).…”
Section: Discussionsupporting
confidence: 90%
“…We do not discard the influence of other modifications in human or nonhuman primate evolution, such as changes in the distribution of glucose between brain and skeletal muscle (47,48) or an overall decrease in basal metabolic rate (49), which might themselves be adaptations to limited energetic availability. Our findings are also compatible with the general essence of the "maternal energy hypothesis," according to which the maternal supply of energy to the fetus may be limiting to brain expansion (23), although the specific link proposed by that hypothesis is between the mother's basal metabolic rate (rather than simply energy availability, as proposed here) and the brain size of her offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Homo erectus, for instance, was clearly more predatory and a larger consumer of animal products than earlier species (Shipman & Walker, 1989). Therefore, a prominent role of meat in the bioenergetic transformations needed to support the development of the human brain has been suggested, acting via increases in the dopaminergic activity (Previc, 2009) and nicotinamide adenine dinucleotide levels (Williams & Dunbar, 2013), and via the fuelling of the cerebral phosphocreatine circuits (Pfefferle et al, 2011).…”
Section: Meat For Brainsmentioning
confidence: 99%